THREE HISTORICAL WAYS O FMAKING SENSE OF POLITICAL: NON-POWER VIEW ON RELATION BETWEEN HISTORY AND POLITICS - Dementavičius, Justinas (Politologija, 2015)
The article introduces three historical and linguistic approaches on political thought (Anglophonic history of ideas (A. O. Lovejoy, Q. Skinner), German conceptual history (R. Koselleck) and French history of political (P. Rosanvallon)), and have se-veral aims. Firstly, it tries to understand and conceptualize some premises of Western academy that could be easily integrated in Lithuanian socio-humanitarian tradition of political researches. On the one hand, it could help for critical understanding of some historical and political studies done in Lithuania in the past years. On the other hand, it shows what kind of problems should be solved if we want to use historical analysis of political in Lithuania. The article tries to present a mode for relating history and politics while looking at them not as power practices, but highlighting historical researches as methodological tool to understand political action and mea-ning of political. While describing three humanitarian perspectives to political science that are concerned with studying political phenomena we can point out several of their common points. Firstly, utterance and political action are closely interrelated. Secondly, all programs emphasizes historical context – past ideas, conceptions and discussions should be seen as meaningful in specific historic period and contravene to our known meanings. Thirdly, all public ideas are presenting some world view or historical rea-lity. At the same time they are instruments used for expressing thoughts (to firm or to change social world or idea system), and objects that could be changed. Fourthly, thoughts expressed in utterance are rational, e. g. understandable in everyday communication at that historical period. Finally, historicity as important cause for transforming ideas, concepts and discussion issues matters for all three schools. All those presuppositions create programs that could help to understand political thought and debates in the new light of history. Also there are some significant differences between three approaches that should be taken in to account if we want to use them in practical analysis. Article points out differences in research strategy (for example, micro- and synchronic analysis used by Skinnerian history of ideas; macro- and diachronic analysis common to conceptual history and some kind of middle way is taken by history of political), scope of research (not all of the approaches recognize importance of national or social context), sources used for analysis (not all historical material is used as meaningful), methodological presumptions and aims of the analysis. This all leads to different concept of politics and what is meant by meaningful political analysis in all three approaches. In the last section of the article we introduce context of current studies of political thought in Lithuania and indicates possible trends for future studies while using more historical approaches to political. It is claimed that all three schools could help deepen our knowledge about Lithuanian political culture, tradition of political thought and transformation of main political concepts in Lithuania. While arguing that article also shows four main problems or trends for future analysis of Lithuanian case: relation with other traditions of political thought; question of Lithuanian political vocabulary; the beginning of modernization and change of meaning of concepts; question of continuity or discontinuity in usage of concepts.